2019
DOI: 10.11646/phytotaxa.404.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Bulbophyllum yarlungzangboense (Orchidaceae; Epidendroideae; Malaxideae), a new species from Tibet, China

Abstract: Bulbophyllum yarlungzangboense, a new species of Orchidaceae from Tibet, China is described and illustrated, it is morphologically similar to B. gamblei and B. shweliense, but can be easy distinguished from the later by petals ovate-oblong, stelidis triangular, base of column foot with V-shape cushion. The new species is tentatively assigned to sect. Desmosanthes based on morphological characters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…These new taxa and records are mainly distributed in southeast Xizang, the Hengduan Mountains and southeast Yunnan, which are regarded as hotspots of orchid diversity as well as hotspots for China's endemic flora in general ( Zhang et al., 2015 ; Huang et al., 2016 ). The majority of our knowledge of orchids from these regions is accumulated from floras ( Chen et al., 2009 ; Xu et al., 2010 ; Jin et al., 2019 ), ongoing regional surveys ( Jin et al., 2018 ; Wang et al., 2018 ) and descriptions of new species ( Hu et al., 2013 ; Averyanov et al., 2015 , 2019 ; Liu et al., 2016a ; Zhai et al., 2017 ; Zhang et al., 2017 ; Cai et al., 2019 ; Li et al., 2019 ; Ya et al., 2019a , b ; Aung et al., 2020 ; Du et al., 2020 ; Yang et al., 2020 ). The geographic distributions of many species remain unknown, and the potential discovery of undescribed orchid species, especially in the shrinking primeval forests of the region, requires continued field work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These new taxa and records are mainly distributed in southeast Xizang, the Hengduan Mountains and southeast Yunnan, which are regarded as hotspots of orchid diversity as well as hotspots for China's endemic flora in general ( Zhang et al., 2015 ; Huang et al., 2016 ). The majority of our knowledge of orchids from these regions is accumulated from floras ( Chen et al., 2009 ; Xu et al., 2010 ; Jin et al., 2019 ), ongoing regional surveys ( Jin et al., 2018 ; Wang et al., 2018 ) and descriptions of new species ( Hu et al., 2013 ; Averyanov et al., 2015 , 2019 ; Liu et al., 2016a ; Zhai et al., 2017 ; Zhang et al., 2017 ; Cai et al., 2019 ; Li et al., 2019 ; Ya et al., 2019a , b ; Aung et al., 2020 ; Du et al., 2020 ; Yang et al., 2020 ). The geographic distributions of many species remain unknown, and the potential discovery of undescribed orchid species, especially in the shrinking primeval forests of the region, requires continued field work.…”
Section: Discussionmentioning
confidence: 99%
“…During botanical surveys in Southwest China from 2017 to 2020, we collected a great number of orchid species. After comparing the morphological features of collected specimens with those of herbarium specimens (i.e., taxa similar to Cheirostylis Blume , Myrmechis Blume and Bulbophyllum Thouars) and consulting relevant literature (for Cheirostylis, see Hemsley, 1895 ; Rolfe, 1896 , 1903 ; Seidenfaden, 1978 ; Jin et al., 2007a , b ; Chen et al., 2009 ; Liu et al., 2016b ; Wu et al., 2020 ; for Myrmechis , see Rolfe, 1903 ; Seidenfaden, 1978 ; Maity et al., 2007 ; for Bulbophyllum , see Summerhayes, 1928 ; Seidenfaden, 1969 , 1979 ; Lin, 1975 ; Tsi, 1989 ; Chen et al., 2009 ; Raskoti and Ale, 2011 ; Vermeulen et al., 2015 ; Averyanov et al., 2015 , 2018 , 2019 ; Liu et al., 2017 ; Zhai et al., 2017 ; Li et al., 2019 ; Ya et al., 2019a ; Ma et al., 2020 ), we confirmed that eight species are new to science and three species are new records for China. Here, these species are described and illustrated…”
Section: Introductionmentioning
confidence: 99%